Uptake and intracellular traffic of siRNA dendriplexes in glioblastoma cells and macrophages - Perez, Ana Paula (2011)
Gene silencing using small interfering RNA (siRNA) is a promising new approach for glioblastoma. The endocytic uptake and delivery of siRNA to intracellular compartments could be enhanced by complexation with polyamidoamine dendrimers.In the present work, the uptake mechanisms and intracellular traffic of siRNA/generation 7 dendrimer complexes (siRNA dendriplexes) were screened in T98G glioblastoma and J774 macrophages. Methods: The effect of a set of chemical inhibitors of endocytosis on the uptake and silencing capacity of dendriplexes was determined by flow cytometry. Colocalization of fluorescent dendriplexes with endocytic markers and occurrence of intracellular dissociation were assessed by confocal laser scanning microscopy. Results: Uptake of siRNA dendriplexes by T98G cells was reduced by methyl-beta-cyclodextrin, genistein, and cytochalasine D, silencing activity was reduced by genistein; dendriplexes colocalized with cholera toxin subunit B. Therefore, caveolin-dependent endocytosis was involved both in the uptake and silencing activity of siRNA dendriplexes. On the other hand, uptake of siRNA dendriplexes by J774 cells was reduced by methyl-beta-cyclodextrin, genistein, chlorpromazine, chloroquine, cytochalasine D, and nocodazole, the silencing activity was not affected by chlorpromazine, genistein or chloroquine, and dendriplexes colocalized with transferrin and cholera toxin subunit B. Thus, both clathrin-dependent and caveolin-dependent endocytosis mediated the uptake and silencing activity of the siRNA dendriplexes. SiRNA dendriplexes were internalized at higher rates by T98G but induced lower silencing than in J774 cells. SiRNA dendriplexes showed relatively slow dissociation kinetics, and their escape towards the cytosol was not mediated by acidification independently of the uptake pathway. Conclusion: The extent of cellular uptake of siRNA dendriplexes was inversely related to their silencing activity. The higher silencing activity of siRNA dendriplexes in J774 cells could be ascribed to the contribution of clathrin-dependent and caveolin-dependent endocytosis vs only caveolin-dependent endocytosis in T98G cells.